Blood sampled from existing peripheral IV cannulae yields results equivalent to venepuncture: a systematic review. Issue 5 (May 2020) - Lesser, Finnian D; Lanham, David A; Davis, Daniel
Summary: Objectives: To establish whether blood samples taken from used peripheral intravenous cannulae are clinically interchangeable with venepuncture. Design: Systematic review. PubMed, Web of Science and Embase were searched for relevant trials. Setting: Trials which compared blood samples from used peripheral intravenous cannulae to venepuncture and provided limits of agreement or data which allowed calculation of limits of agreement. Participants: Seven trials with 746 participants. Blood tests included 13 commonly ordered biochemistry, haematology and blood gas measurements. Main outcome measures: 95% limits of agreement. Data were pooled using inverse variance weighting and compared to a clinically acceptable range estimated by expert opinion from previous trials. Results: Limits of agreement for blood samples from used peripheral intravenous cannulae were within the clinically acceptable range for sodium, chloride, urea, creatinine and haematology samples. Limits of agreement for potassium were ±0.47 mmol/L which exceeded the clinically acceptable range. Peripheral intravenous cannula samples for blood gas analysis gave limits of agreement which far exceeded the clinically acceptable range. Conclusions: Blood sampling from used peripheral intravenous cannulae is a reasonable clinical practice for haematology and biochemistry samples. Potassium samples from used peripheral intravenous cannulae can be used in situations where error up to ±0.47 mmol/L is acceptable. Peripheral intravenous cannula samples should not be used for blood gas analysis.